Comparative Analysis of Listening Comprehension Among Grade 10 Students in Public and Private Schools in Pikit, North Cotabato, Philippines - Abdula, Maleha Guiamalon; Subillaga, Rebecca Dampil (ELT Worldwide: Journal of English Language Teaching, 2025)
This study examined the level of listening comprehension skills of Grade 10 students in public and private high schools in Pikit, North Cotabato, Philippines, addressing the limited empirical evidence comparing listening sub-skills across school types in the local Philippine context. Specifically, it examined the relationship between the respondents’ sex and ethnicity and their comprehension performance across four domains: speaker’s purpose, sequencing of details, vocabulary, and conclusion and valid inference. A total of 277 students participated, comprising 201 public school and 76 private school students. Data were gathered using researcher-made and adapted listening comprehension assessments and were analyzed using descriptive statistics, multiple linear regression analysis, and z-tests for independent samples. Results revealed that in public schools, sex and ethnicity were significant predictors of performance in speaker’s purpose (R² = 0.062, p = 0.002) and conclusion and valid inference (p = 0.022 for sex). In private schools, regression analysis showed that ethnicity significantly predicted vocabulary scores (R² = 0.249, p < 0.001) and conclusion and valid inference (R² = 0.163, p = 0.002). Z-tests indicated a significant difference between public and private school students in speaker’s purpose (z = 2.62) and conclusion and valid inference (z = 2.59), favoring private schools in the former and public schools in the latter. Overall mean scores for public and private schools were 74.78 and 74.73, respectively, both categorized as "Beginning" level. These findings suggest that while overall performance remains low, specific personal variables significantly impact listening comprehension in different school settings. This study contributes to comparative listening comprehension research by highlighting how personal variables operate differently across school contexts and by providing localized evidence that challenges assumptions about uniform listening skill development under a standardized curriculum.